2011
DOI: 10.1177/1948550611429024
|View full text |Cite
|
Sign up to set email alerts
|

Disgust Sensitivity, Political Conservatism, and Voting

Abstract: In two large samples (combined N = 31,045), we found a positive relationship between disgust sensitivity and political conservatism. This relationship held when controlling for a number of demographic variables as well as the “Big Five” personality traits. Disgust sensitivity was also associated with more conservative voting in the 2008 U.S. presidential election. In Study 2, we replicated the disgust sensitivity–conservatism relationship in an international sample of respondents from 121 different countries. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
223
5
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 316 publications
(253 citation statements)
references
References 27 publications
24
223
5
1
Order By: Relevance
“…For the purposes of this study the phrase 'disgust sensitivity scale' has been used for all versions of the scale for simplicity. Research using the disgust sensitivity scale has found it negatively correlates with age, 34 positively correlates with political conservatism, 35 and that females have a significantly higher rating than males.…”
Section: Measuring Disgustmentioning
confidence: 99%
“…For the purposes of this study the phrase 'disgust sensitivity scale' has been used for all versions of the scale for simplicity. Research using the disgust sensitivity scale has found it negatively correlates with age, 34 positively correlates with political conservatism, 35 and that females have a significantly higher rating than males.…”
Section: Measuring Disgustmentioning
confidence: 99%
“…Some social demography statistical indicators, such as gender, age, and academic level, are found to be accurate indicators for predicting the degree of the public's perception regarding the risk of reclaimed water reuse [9]. In sociological studies, the aversion to reclaimed water has been found to be positively correlated with the degree of political conservatism [10]. In addition, there are also other individual and cultural values that affect the public attitudes toward the reuse of reclaimed water reuse.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with nonmoral emotions, moral emotions are those that are most often associated with evaluations of societal norms (11) and are elicited by interests that may go beyond self-interest [e.g., contempt in response to injustices committed in another country (12)]. Importantly, moral emotions may also be tied specifically to behavior that is relevant to morality and politics, including judgments of responsibility and voting (13,14). Thus, emotions can be roughly divided into classes of "moral emotions" and "nonmoral emotions" that are associated with distinct appraisals, eliciting conditions, and functional outcomes.…”
mentioning
confidence: 99%